APPLYING CONTEMPLATIVE EDUCATION TO DEVELOP STUDENT QUALITY IN CIVIC DUTY COURSES AT DARAPITTAYAKOM SCHOOL, UTTARADIT PROVINCE - (Autcharapun Phoemkhuen), อัจฉราพรรณ เพิ่มขึ้น; (Kanya Kumsiripiman), กัญญา กำศิริพิมาน; (Charin Mangkhang), ชรินทร์ มั่งคั่ง (Journal of Education and Innovation, 2018)
The purposes of this research were to investigate; 1) the result of applying Contemplative Education to develop student quality in Civic Duty courses, and 2) The opinions of the students towards Contemplative Education to develop student quality in Civic Duty courses. The population for this research was 31 of ninth grade students who were studying in the second semester of the school year 2015 at the Darapittayakom School, Ban Dara sub-district, Phichai district, Uttaradit Province. The tools for the research were 1) seven study plans for Civic Duty courses, which were divided into 26 classes, 50 minutes of each class. The researcher employs 2 classes for each learning activity which consists of 5 steps (Check-in, Dialogue Conversation, Reflection, Check-out, and Journaling), 2) the students assessment form for Contemplative Education in Civic Duty courses, and 3) the questionnaires for the students regarding the opinions and perspective towards applying Contemplative Education to develop student quality in Civic Duty courses. The statistical techniques including percentage mean and standard deviation are utilized to analyze data. The result of the survey suggests that applying Contemplative Education to develop the quality of ninth grade students at the Darapittayakom School in Civic Duty courses has very good outcome with the average level of 2.56, and the students also have positive attitudes towards the process of practicing Contemplative Education with the average level of 4.39.